2019
DOI: 10.1177/2158244019861488
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Research Synthesis of Literature on Teaching Qualitative Research Methods

Abstract: This article surveys the literature from 1999 to 2013 on teaching qualitative research methods. One hundred thirteen articles fitted the inclusion criteria; 79 of these were by academics in the United States and Canada. Only 39 of the 113 were based on empirical research: from these, seven descriptive themes were distilled, of which the dominant ones are experiential learning and practice-based materials and workshops. The literature portrayed teaching qualitative research as providing experiential and practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 60 publications
1
30
0
4
Order By: Relevance
“…With this in mind, the research was centered on the practice approach of experiential learning suggested by Bartels and Wagenaar (2018). Experiential learning is the most widely used practice in teaching qualitative research (Wagner, Kawulich, & Garner, 2019). Viewing experiential learning as performative, indexical, reflective, and holistic, Bartels and Wagenaar (2018) argue that experiences of students and instructors are pivotal in learning and teaching qualitative research and that learning to do qualitative research means more than acquiring knowledge about varying methodologies and skills required for applying certain methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With this in mind, the research was centered on the practice approach of experiential learning suggested by Bartels and Wagenaar (2018). Experiential learning is the most widely used practice in teaching qualitative research (Wagner, Kawulich, & Garner, 2019). Viewing experiential learning as performative, indexical, reflective, and holistic, Bartels and Wagenaar (2018) argue that experiences of students and instructors are pivotal in learning and teaching qualitative research and that learning to do qualitative research means more than acquiring knowledge about varying methodologies and skills required for applying certain methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The design, methods and approaches used captured, processed, analysed and interpreted the data drawn from the positivist and constructivist philosophical schools, which are complementary ontologically, epistemologically and methodologically (Castleberry and Nolen, 2018;Wagner et al, 2019). Based on the schools of thought, both quantitative and qualitative methods were applied to capture primary data on learners' prediction practices when reading texts and scores in the post-intervention test, which was designated, learners' achievement in reading comprehension passages.…”
Section: Methodsmentioning
confidence: 99%
“…Conhecimento esse que até, em alguns trechos, parece enviesado e dicotómico, como acontece em várias narrativas sobre a importância "exclusiva" da metodologia qualitativa para o desenvolvimento de teorias e para a exploração e abordagem inicial ao estudo de um fenómeno. Aqui, parecenos surgir de alguma forma o condicionamento da formação prévia, sobretudo, em investigação quantitativa, e também a necessidade de formação com enfâse na metodologia qualitativa e na especificidade da sua linguagem Roberts & Castel, 2016;Wagner et al, 2019).…”
Section: Discussão E Conclusõesunclassified
“…Quanto à questão sobre as expectativas dos alunos sobre a UC de métodos de investigação qualitativa, antes da sua frequência, os dados foram agrupados em dois tópicos, isto é, Por outro lado, encontra-se de alguma forma essa justificação quando se referem ao Processo de ensino-aprendizagem, destacando-se a Aprendizagem de conhecimentos e competências bem como a Transferência da aprendizagem, destacando-se, mais uma vez, a Aplicação da aprendizagem efetuada na dissertação, na prática profissional ou noutros estudos futuros, ainda que aqui não se destaque a aplicação na dissertação como no tópico anterior. Mais uma vez nos parece que estes dados traduzem a abertura dos alunos ao conhecimento e ao investimento nesta UC, antecipando-se que a frequência das aulas lhes possa fornecer conteúdos e competências de investigação para aprofundamento dos temas abordados, clarificando a possível aplicação ao mundo profissional (Thorpe, 2013;Wagner, et al, 2019). algumas limitações do estudo.…”
Section: Discussão E Conclusõesunclassified
See 1 more Smart Citation